IbM SMP NEGERI 4 DENPASAR - Ida Bagus Ari Arjaya; Cokorda Javandira (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
SMP 4 Denpasar holds the title of